Canadian Women in Otolaryngology—Head and Neck Surgery part 1: the relationship of gender identity to career trajectory and experiences of harassment - Khrystyna Ioanidis; Kendra Naismith; Agnieszka Dzioba; S. Danielle MacNeil; Josée Paradis; Smriti Nayan; Julie E. Strychowsky; M. Elise Graham (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Introduction Women in surgical specialties face different challenges than their male peers. However, there is a paucity of literature exploring these challenges and their effects on a Canadian surgeon’s career. Methods A REDCap® survey was distributed to Canadian Otolaryngology–Head and Neck Surgery (OHNS) staff and residents in March 2021 using the national society listserv and social media. Questions examined practice patterns, leadership positions, advancement, and experiences of harassment. Gender differences in survey responses were explored. Results 183 completed surveys were obtained, representing 21.8% of the Canadian society membership [838 members with 205 (24.4%) women]. 83 respondents self-identified as female (40% response rate) and 100 as male (16% response rate). Female respondents reported significantly fewer residency peers and colleagues identifying as their gender (p < .001). Female respondents were significantly less likely to agree with the statement “My department had the same expectations of residents regardless of gender” (p < .001). Similar results were observed in questions about fair evaluation, equal treatment, and leadership opportunities (all p < .001). Male respondents held the majority of department chair (p = .028), site chief (p = .011), and division chief positions (p = .005). Women reported experiencing significantly more verbal sexual harassment during residency (p < .001), and more verbal non-sexual harassment as staff (p = .03) than their male colleagues. In both female residents and staff, this was more likely to originate from patients or family members (p < .03). Discussion There is a gender difference in the experience and treatment of OHNS residents and staff. By shedding light on this topic, as a specialty we can and must move towards greater diversity and equality. Graphical Abstract